Performance Evaluation of Agricultural Extension Services in Ambon City - Ivakdalam, Lidya Maria; Tupamahu, Yonette Maya; Pentury, Melkhianus Hendrik (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to analyze the level of importance and implementation, as well as the suitability of performance attributes of agricultural extension services. The analysis method uses gap analysis or gaps. The results showed that the attributes were classified as very important, namely: Serious attention (P5), Reliability in seeking facilities and infrastructure (P8), Reliability in helping farmers/farmer groups in preparing farming activity plans (P9), Reliability in helping farmer groups in making group administration (P9) P10), The instructor's reliability for increasing business results (P14), The instructor's willingness to provide services quickly (P15), The instructor's willingness to help the difficulties faced by the farmers (P16), The instructor's time to respond quickly to farmers' requests (P17), Accuracy in handling farmer's complaints (P18), Extension officers have the competence to guide, solve problems of farmers/farmer groups in the field, and establish business partnerships in agriculture (P19), Extension officers are polite and friendly (P20), Extension officers have the knowledge and skills to provide clear and easy information understandable (P21), and Easy to find and contact for consultation (P24). The prioritized attributes are improved, namely P17, P18, Reliability of agricultural instructors in conveying information on business opportunities and capital (P13), Counseling is carried out on time (P4), P15, Serious attention from instructors to farmers (P5), P9, Reliability in conveying latest technology (P11), P16, Reliability in conveying market information (P12), Training and regular visits (P7), P14, P8, P19, Paying special/individual attention (P26), and P24.